2019
DOI: 10.1002/jmri.26901
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics and Machine Learning With Multiparametric Preoperative MRI May Accurately Predict the Histopathological Grades of Soft Tissue Sarcomas

Abstract: Background Preoperative prediction of the grade of soft tissue sarcomas (STSs) is important because of its effect on treatment planning. Purpose To assess the value of radiomics features in distinguishing histological grades of STSs. Study Type Retrospective. Population In all, 113 patients with pathology‐confirmed low‐grade (grade I), intermediate‐grade (grade II), or high‐grade (grade III) soft tissue sarcoma were collected. Field Strength/Sequence The 3.0T axial T1‐weighted imaging (T1WI) with 550 msec repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 37 publications
0
49
0
1
Order By: Relevance
“…Corino et al [34] reported that a radiomics classi er based on apparent diffusion coe cients in 19 patients could be used to distinguish grade II from III STS. Xiang et al [35] found that quantitative MRI-based histogram parameters can differentiate the grade of STS, Zhang et al [17] demonstrated that FS-T2WI-based radiomics could be used to predict the histopathological grade of STS in a study with a small cohort of 35 patients, and Wang et al [18] found that radiomics signature-based machine-learning classi ers can distinguish low-grade from high-grade STS. Nevertheless, these studies had small sample cohorts and two of them lacked a validation set, which potentially lead to the problem of over tting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Corino et al [34] reported that a radiomics classi er based on apparent diffusion coe cients in 19 patients could be used to distinguish grade II from III STS. Xiang et al [35] found that quantitative MRI-based histogram parameters can differentiate the grade of STS, Zhang et al [17] demonstrated that FS-T2WI-based radiomics could be used to predict the histopathological grade of STS in a study with a small cohort of 35 patients, and Wang et al [18] found that radiomics signature-based machine-learning classi ers can distinguish low-grade from high-grade STS. Nevertheless, these studies had small sample cohorts and two of them lacked a validation set, which potentially lead to the problem of over tting.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, MRI-based radiomics would be broadly applicable to patients with sarcomas. Radiomics has been successfully applied in prediction of the histologic grade, local recurrence or distant metastasis, overall survival, and response to neoadjuvant therapy in patients with STSs [17][18][19][20][21][22]. Most previous reports de ned high-grade STS as grades II and III, while we de ne high-grade STS as grade III based on recently published studies [6,22].…”
mentioning
confidence: 99%
“…The biomarkers included in the model cover different biological scales from molecular to phenotypic [15] . Radiomics in the application of skeletal muscle system is usually in terms of bone tumors, such as bone disease diagnosis and differential diagnosis of tumor [16,17] , prediction [18] of tumor complications, the prognosis of tumor treatment pathologic grading [19][20] and tumor, a small study applies beside the osteoporosis [21] , vertebral abscess [22] , temporo-mandibular joint osteoarthritis [23] , postoperative infection and in ammation [24] , and so on. Few radiomics studies have been conducted on LHD.…”
Section: Discussionmentioning
confidence: 99%
“…There are small number of recent studies which have predicted grade of soft-tissue sarcoma using texture analysis. [ 22 24 ] They performed texture analysis based on only ADC maps or fat suppressed T2-weighted images or T1- and T2-weighted images. We used T1- and T2-weighted images and fat-suppressed CE T1-weighted images for texture analysis.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 ] Texture analysis has been studied to predict tumor stage and survival in various cancers, [ 12 16 ] differentiate benign from malignant lesions in breast, [ 17 , 18 ] and to predict treatment response in various other cancers. [ 19 21 ] To our knowledge, however, there have been a small number of studies [ 22 24 ] investigating whether texture analysis based on 3T preoperative MRI can predict the grade of soft-tissue sarcomas.…”
Section: Introductionmentioning
confidence: 99%